Age of Infection with Kaposi Sarcoma Associated Herpesvirus and Subsequent Antibody Values Among Children in Uganda - Nalwoga, Angela (Pediatr Infect Dis J, 2018)
We investigated associations between KSHV seroconversion age and KSHV antibody values in Ugandan children. Every annual delay in KSHV seroconversion age was associated with a reduction of 19% (p<0.0001) in K8.1 and 27% (p<0.0001) in ORF73 antibody values at age 6. Early infection may be an important risk factor for KSHV pathogenesis and viral shedding in saliva, leading to transmission.